RFRP-3, the Mammalian Ortholog of GnIH, Is a Novel Modulator Involved in Food Intake and Glucose Homeostasis - Huo, Konglin; Li, Xun; Hu, Wen; Song, Xingxing; Zhang, Duoni; Zhang, Xin; Chen, Xinyi; Yuan, Jingzhi; Zuo, Jianyu; Wang, Xiaoye (Frontiers in Endocrinology, 2020)
RF amide-related peptide 3 (RFRP-3), the mammalian ortholog of gonadotropin-inhibitory hormone (GnIH), is a reproductive inhibitor and an endogenous orexigenic neuropeptide that may be involved in energy homeostasis. In this study, we evaluated the effect of acute or chronic RFRP-3 treatment (administered via intraperitoneal injection) on the food intake, meal microstructure and weight of rats, as well as the mechanism through which RFRP-3 is involved in glucose metabolism in the pancreas and glucose disposal tissues of rat in vivo. Our results showed that the intraperitoneal administration of RFRP-3 to rats resulted in marked increases in hyperphagia, obesity, hyperglycemia, glucose intolerance, hypoinsulinism, hyperglucagon and insulin resistance, as well as significant increases in the size of pancreatic islets and the inflammation reaction. Thus, we strongly propose that RFRP-3 is a novel neuroendocrine regulator of glucose metabolism that may be a potential therapeutic target for glucose metabolic disorders caused by diabetes and obesity.